Current developments in pharmacotherapy for actinic keratosis. (13th October 2018) - Campione, Elena; Ventura, Alessandra; Diluvio, Laura; Mazzeo, Mauro; Mazzilli, Sara; Garofalo, Virginia; Di Prete, Monia; Bianchi, Luca
ABSTRACT: Introduction: Actinic keratosis (AK) is a superficial squamous cell carcinoma (SCC) where chronic sun exposure playing central role in its pathogenesis. UVB causes direct damage to DNA, producing pyrimidine dimers, and suppressing the protective role of p53. The stepwise progression of AK, with increased expression of anti-apoptotic Bcl-2, favors progression to SCC. Moreover, the dermal response characterized by inflammation and mediated by prostaglandins is a critical component of tumorigenesis that promotes tumor growth, tissue invasion, angiogenesis and metastasis. Other risk factors are represented by age, gender, phototype and drugs. Areas covered: In this review, the authors document the recent developments of different therapies used to treat AK and provide their perspectives on current and future treatment strategies. Expert opinion: The usefulness of long-term treatment with piroxicam and sun filters or diclofenac targeting the inflammation phases of skin tumorigenesis favors AK's healing and provides greater control of the cancerization field. Nonsteroidal anti-inflammatory drugs can be safely used in patients who use photosensitizing drugs and, therefore, are more at risk of developing skin tumors. Immunomodulatory therapies, which require shorter treatment, are characterized by more common local side effects, and need more attention by the dermatologist in the concern of patient education, resulting essential to improve adherence and outcomes.